PHYTOCHEMICAL ANALYSIS AND SCREENING THE BIOLOGICAL ACTIVITIES OF UNRIPE PODS OF PONGAMIA GLABRA VENT - RAVISANKAR, NARAYANAN; KAYALVIZHI, R.; BHARATHI, KUPPUVELSAMY VANITHA (International Journal of Applied Pharmaceutics, 2022)
Objective: Pongamia glabra vent is widely used in folk medicine. The chemicals found in these have gained prominence in various studies. The phytochemical constituents of the benzene extract of the unripe pods of Pongamia Glabra Vent were investigated qualitatively and quantitatively using standard methods. Methods: The compounds belonging to the group of flavonoids were isolated from benzene extracts of unripe pods of Pongamia Glabra Vent. Results: A total six known natural compounds were separated and purified by chromatography techniques and five compounds were isolated and identified as flavonoid derivatives such as lanceolatin B, Karanjin, Pongapin, Kanjone, Pinnatin and the other one is a furanodibenzoyl methane namely Pongamol. Conclusion: Physical studies such as UV, IR, 1H and 13C NMR, Mass and Element analysis have been used to confirm the structures of the isolated compounds. In the study, all compounds exhibited strong antibacterial activity against selected bacteria and fungi. The compound of C06 showed better antioxidant performance compared to standard ascorbic acid and butylated hydroxytoluene.